Formulation and optimization of orodispersible tablets of flutamide - Elkhodairy, Kadria A. (2013)
The present study aimed to formulate orodispersible tablets of flutamide (FTM) to increase its bioavailability. Orodispersible tablets were prepared by direct compression technique using three different approaches namely; super-disintegration, effervescence and sublimation. Different combined approaches were proposed and evaluated to optimize tablet characteristics. Sodium starch glycolate (SSG) was used as the superdisintegrant. The prepared powder mixtures were subjected to both pre and post compression evaluation parameters including; IR spectroscopy, micromeritics properties, tablet hardness, friability, wetting time, disintegration time and in-vitro drug release. IR studies indicated that there was no interaction between the drug and the excipients used except Ludipress. The results of micromeritics studies revealed that all formulations were of acceptable to good flowability. Tablet hardness and friability indicated good mechanical strength. Wetting and dispersion times decreased from 46 to 38 s by increasing the SSG concentration from 3.33 to 6.66% w/w in tablets prepared by superdisintegration method. The F8 formulation which was prepared by combined approaches of effervescence and superdisintegrant addition gave promising results for tablet disintegration and wetting times but failed to give faster dissolution rate. The incorporation of 1:5 solid dispersion of FTM: PEG 6000 instead of the pure drug in the same formulation increased the drug release rate from 73.12 to 96.99% after 15 min. This increase in the dissolution rate may be due to the amorphization of the drug during the solid dispersion preparation. The presence of the amorphous form of the drug was shown in the IR spectra.